The New Puberty : Navigating Girls' Early Development in Today's World - Greenspan, Louise; Deardorff, Julianna (Emmaus, Pennsylvania : Rodale Books, 2014)
"The coming-of-age experience has changed dramatically, with girls maturing sooner than ever. But what happens when a girl has the body of a 13-year-old and the brain of an 8-year-old? Contrary to popular wisdom, early puberty is not merely a reflection of physical changes--it's deeply psychological, too, with effects that can put a girl at higher risk for behavioral problems and long-term health challenges, such as obesity, depression, eating disorders, and even cancer.The New Puberty is a reassuring, empowering guide for millions of parents--as well as teachers, coaches, pediatricians, and family members--by two notable experts in the field. Compiling original research and clinical experience, Drs. Greenspan and Deardorff offer practical strategies for supporting girls entering this complex stage of their lives. Readers will learn why girls are developing faster than they did a generation ago (it's not just environmental toxins); the potential physical and emotional consequences; how to tell if a girl has reached puberty early and what to do; and how to initiate and continue difficult conversations. Impeccably researched, comfortingly prescriptive, and a timely antidote to sensationalistic headlines, The New Puberty provides the roadmap to help young girls move forward with confidence, ensuring their optimal health and happiness for the future"--
Includes bibliographical references and index.
Keywords: Puberty; Teenage girls -- Physiology; Teenage girls -- Growth; Teenage girls -- Health and hygiene; Parenting; HEALTH & FITNESS / Children; FAMILY & RELATIONSHIPS / Life Stages / Adolescence